Polymorphism in magic-sized Au144(SR)60 clusters - Kirsten M.Ø. Jensen (Nature Portfolio, 2016)
Gold nanoclusters are important nanomaterials but their structural assignment can be challenging if single crystals can’t be grown. Here, the authors use pair distribution function analysis of X-ray powder diffraction data for Au144(SR)60nanoclusters, and show that they exhibit polymorphism.